2008
DOI: 10.1111/j.1600-0463.2008.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins 27, 60 and 70 as prognostic markers of prostate cancer

Abstract: Heat shock proteins (HSPs) protect cells against stress-associated injury and are overexpressed in several malignant tumors. We aimed to investigate their value as prognostic markers in prostate cancer. A tissue microarray (TMA) was constructed of 289 prostate cancers from radical prostatectomy (RP) specimens with median follow-up of 48.9 months. Slides were immunostained for HSP27, HSP60 and HSP70. Intensity and extent of immunoreactivity (IR) and their product (IRp) was evaluated by two observers. The IRp of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 27 publications
(38 reference statements)
5
54
2
1
Order By: Relevance
“…32 The HSPB1 level increases after androgen suppression and is cytoprotective in hormone-refractory PCa. 33,34 In our study, the HSPB1 increase was shown by iTRAQ analysis and qRT-PCR, suggesting its implication in the natural progression of PCa and the tumour response to DES.…”
Section: Discussionsupporting
confidence: 55%
“…32 The HSPB1 level increases after androgen suppression and is cytoprotective in hormone-refractory PCa. 33,34 In our study, the HSPB1 increase was shown by iTRAQ analysis and qRT-PCR, suggesting its implication in the natural progression of PCa and the tumour response to DES.…”
Section: Discussionsupporting
confidence: 55%
“…Frequently, the immunopositivity for Hsp60, in cancerous tissue or circulating cancer cells, correlates with a poor prognosis [49,[51][52][53]. In contrast to these findings, we previously found that the loss of Hsp60 immunopositivity can be related to development and progression of bronchial cancer [54], which reflects the variety of roles that Hsp60 can play.…”
Section: Discussionmentioning
confidence: 73%
“…As such, the chaperonin has become the subject of studies aiming at determining its precise role as etiologic-pathogenic factor and also aiming at inventing new diagnostic and therapeutic ways centered on it. Adrenal gland Adrenal Cushing's tumor [168] Bladder Transitional cell carcinoma; carcinosarcoma [169][170][171] Bone marrow, blood, lymph nodes Acute myeloid leukemia; Hodgkin's lymphoma [155,[172][173][174] Brain Astroglyoma; glioblastoma; meningioma [175][176][177][178][179] Breast Breast ductal carcinoma [180,181] Esophagus Oesophageal carcinoma [182,183] Large bowel Adenocarcinoma [23,169,[184][185][186][187] Liver Hepatocellular carcinoma [188] Lung Bronchial carcinoma [25,26,189,190] Ovary Serous ovarian cancer [191] Prostate Prostate carcinoma [24,[192][193][194] Stomach Gastric maltoma [195] Uterus Exocervical carcinoma [22,196] Adapted from [2]. ATP synthase [197] Dihydrofolatereductase [37,46] Hsp10 [37,41] Human Carbonicanhydrase II [37,198,…”
Section: Expert Opinionmentioning
confidence: 99%